High volumetric-energy-density flexible supercapacitors based on PEDOT:PSS incorporated with carbon quantum dots hybrid electrodes - Nguyen, Dinh Cung Tien; Kim, Seonghan; Kim, Bo-Seok; Kim, Sejung; Lee, Soo-Hyoung (Chinese Society of Metals, 2025)
Poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is a highly successful conductive polymer utilized as an electrode material in energy storage units for portable and wearable electronic devices. Nevertheless, employing PEDOT:PSS in supercapacitors (SC) in its pristine state presents challenges due to its suboptimal electrochemical performance and operational instability. To surmount these limitations, PEDOT:PSS has been integrated with carbon-based materials to form flexible electrodes, which exhibit physical and chemical stability during SC operation. We developed a streamlined fabrication process for high-performance SC electrodes composed of PEDOT:PSS and carbon quantum dots (CQDs). The CQDs were synthesized under microwave irradiation, yielding green- and red-light emissions. Through optimizing the ratios of CQDs to PEDOT:PSS, the SC electrodes were prepared using a spray-coating technique, marking a significant improvement in device performance with a high volumetric capacitance (104.10 F cm(-3)), impressive energy density (19.68 Wh cm(-3)), and excellent cyclic stability, retaining similar to 85 % of its original volumetric capacitance after 15,000 repeated GCD cycles. Moreover, the SCs, when utilized as a flexible substrate, demonstrated the ability to maintain up to similar to 85 % of their electrochemical performance even after 3,000 bending cycles (at a bending angle of 60 degrees). These attributes render this hybrid composite an ideal candidate for a lightweight smart energy storage component in portable and wearable electronic technologies.(c) 2025 Published by Elsevier Ltd on behalf of The editorial office of Journal of Materials Science & Technology.